1998
DOI: 10.1074/jbc.273.13.7320
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein MCM6 on HeLa Cell Chromatin

Abstract: Mcm proteins have recently attracted considerable attention because they are thought to perform an essential function in the regulation of chromatin replication (reviewed in Refs. 1 and 2). Eukaryotic cells express six evolutionarily conserved Mcm proteins. They were so named because the first members of this family of nuclear proteins were discovered through genetic screens of yeast mutants unable to maintain the extrachromosomal replication of minichromosomes (Mcm, minichromosome maintenance) 1 (3). Mcm prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
(47 reference statements)
4
25
1
Order By: Relevance
“…5E). Similar results have been reported in yeast, mouse, and frog, where MCM4, MCM6, and MCM7 form a "core" complex that is more tightly associated with chromatin than the remaining subunits (Ishimi et al, 1996;Coue et al, 1998;Holthoff et al, 1998;Lee and Hurwitz, 2000;Prokhorova and Blow, 2000;Davey et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…5E). Similar results have been reported in yeast, mouse, and frog, where MCM4, MCM6, and MCM7 form a "core" complex that is more tightly associated with chromatin than the remaining subunits (Ishimi et al, 1996;Coue et al, 1998;Holthoff et al, 1998;Lee and Hurwitz, 2000;Prokhorova and Blow, 2000;Davey et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…In parallel assays, the majority of the chromatin marker HMGA remained associated with the pellet fraction, establishing that our extraction protocol does not result in widespread dissociation of chromatin and cannot account for the bulk of MCM5 and MCM7 in the soluble fraction. In asynchronous, immortalized human cells, the nonchromatin-bound fraction of MCM ranges from slightly more than half (Holthoff et al, 1998;Mendez and Stillman, 2000) to approximately 90% of the total cellular protein (Burkhart et al, 1995). A significant fraction of the non-chromatin-bound MCM in the Arabidopsis culture may have originated from cells that have exited the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using immunoprecipitation, gradient centrifugation, and gel filtration techniques have shown that the MCM proteins form various subcomplexes composed of different members of the family, such as MCM5͞3 or MCM4͞6͞7 subcomplexes at varying salt concentrations (40,41,(43)(44)(45)(46). To see the pattern of MCM complexes and Stat1 in IFN-␥-treated cells, nuclear extracts were prepared from BUD-8 cells untreated or treated with IFN-␥ for 30 min and subjected to gel filtration followed by SDS͞PAGE and Western blotting analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The MCMs form complexes of various constitution (35,40,44), assemble at the initiation site of DNA replication along with other protein complexes such as originrecognition complex (48), and travel together with the replisome (49,50). The MCMs have common structural features such as DNA-dependent ATPase domains characteristic of DNA helicases (39).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular structure and in vitro analyses of these proteins suggest that they function as a DNA helicase (3); they form a heterohexamer complex that binds to DNA replication origins and moves along with the DNA polymerase during DNA replication elongation (4,5). In addition to the hexamer complex, the MCM proteins also form subcomplexes containing some members of the family, such as MCM4͞6͞7 or MCM3͞5 (3,(6)(7)(8). It has been suggested that these subcomplexes represent segments during the assembly of the hexameric MCM complex (9).…”
mentioning
confidence: 99%